Imaging Membrane Order and Dynamic Interactions in Living Cells with a DNA Zipper Probe. (22nd December 2021) - Bagheri, Yousef; Ali, Ahsan Ausaf; Keshri, Puspam; Chambers, James; Gershenson, Anne; You, Mingxu
Abstract: The cell membrane is a dynamic and heterogeneous structure composed of distinct sub‐compartments. Within these compartments, preferential interactions occur among various lipids and proteins. Currently, it is still challenging to image these short‐lived membrane complexes, especially in living cells. In this work, we present a DNA‐based probe, termed "DNA Zipper", which allows the membrane order and pattern of transient interactions to be imaged in living cells using standard fluorescence microscopes. By fine‐tuning the length and binding affinity of DNA duplex, these probes can precisely extend the duration of membrane lipid interactions via dynamic DNA hybridization. The correlation between membrane order and the activation of T‐cell receptor signaling has also been studied. These programmable DNA probes function after a brief cell incubation, which can be easily adapted to study lipid interactions and membrane order during different membrane signaling events. Abstract : Cholesterol‐modified programmable DNA probes are developed to image transient interactions and membrane order in live cell membranes. The membrane order during the activation of T‐cell receptor signaling has also been measured.